Women's health : (Ohio State University Press, 1997)
Challenging purely biomedical definitions of women's health, Women's Health: Complexities and Differences draws attention to social, cultural, and behavioral elements crucial to a broader understanding of the issues. The contributors to this volume raise important questions about the directions currently being taken to improve women's health in the United States: Is women's health merely the absence of disease?